Past and Future Work at the International Labour Organization: Labour as a Fictitious Commodity, Countermovement and Sustainability - Novitz, Tonia (International Organizations Law Review, 2020)
This article analyses past and future work at the International Labour Organization (‘ILO’) with reference to the transformational analysis offered by Karl Polanyi, examining how constitutional statements made through ILO Declarations reflect countermovement to market dominance. These policy shifts at the ILO are also analysed in relation to the three pillars of sustainability (environmental, economic and social), which arguably map onto Polanyi’s three fictitious commodities (with a focus on labour as emblematic of social concerns). It is argued that the emphasis on social justice and sustainability in the 2019 ILO Global Commission Report, including the proposal for a Universal Labour Guarantee, provides significant resistance to the economic orthodoxy regarding the future of work promoted by the World Bank Group and the Organization for Economic Cooperation and Development (‘OECD’). However, this narrative of ILO countermovement also exposes a lack of balanced regulation which requires more inclusive voice on the global stage.
Keywords: ILO; countermovement; fictitious commodities; future; labour; sustainability; voice; work